Evaluation and prevention of natural risks (Taylor & Francis, 2007)
Historical analysis carried out in the Piemonte-territory in north-western Italy, focusing on the consequences of hydrogeological risks, reveals that damage is continually increasing. This can partly be explained by the consistent expansion of urbanized areas at the expense of areas that are essential to the natural modelling processes of the region; the damage resulting from hydrogeological instability often being associated with incompatible territorial decisions. This text gives a detailed account of a series of experiences related to activities that ARPA Piemonte has carried out focusing on the cognitive and forecasting aspects related to risk assessment and alerting procedures.